Contact Across a Diseased Boundary: Urban Space and Social Interaction During Winnipeg’s Influenza Epidemic, 1918-1919 - Jones, Esyllt (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2002)
AbstractDuring the influenza epidemic of 1918-1919 in Winnipeg, several hundred predominantly Anglo-Canadian middle- and upper-class women volunteered to nurse and feed victims of the disease, particularly the poor of the city's north end. The contact between victim and volunteer, north and south, promoted a sense of social order, but was simultaneously unsettling for the women involved and for the broader community. The paper utilizes Mary Louise Pratt's notion of “contact zone” to suggest that the extraordinary qualities of social interaction during the epidemic, when lives normally lived apart intersected, were a source of social tension. This tension was partially resolved through limitations upon who fit the role of volunteer, principles of scientific management and professionalism, and the construction of an ideal feminine heroine. Individual women's volunteerism nevertheless reflected a more ambiguous experience.